2015
DOI: 10.1007/s12328-015-0577-8
|View full text |Cite
|
Sign up to set email alerts
|

A case of a stomach gastrointestinal stromal tumor with extremely predominant cystic formation

Abstract: A 79-year-old male was referred to the hospital with a history of abdominal discomfort. Abdominal computed tomography revealed a cystic tumor with irregular wall thickness, approximately 50 mm in diameter, along the lesser curvature of the gastric body. Magnetic resonance imaging visualized the mass as signal-hyperintense on T2-weighted imaging. Esophagogastroduodenoscopy showed a submucosal tumor with normal mucosa. Surgery was performed and the 60 × 50 × 50 mm mass was resected. The resected tumor comprised … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Small cystic areas are frequently observed in GISTs with large size, but GISTs rarely manifest predominantly as cystic tumors. Cases of this uncommon form have been described but no retrospective study has been reported in the English literature (Hamza et al 2016 ; Okano et al 2015 ; Shaikh et al 2015 ; Sun et al 2016 ; Takahashi et al 2010 ; Wang et al 2017 ; Zhu et al 2014 ). In addition, clinical follow-up information was not available in most cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small cystic areas are frequently observed in GISTs with large size, but GISTs rarely manifest predominantly as cystic tumors. Cases of this uncommon form have been described but no retrospective study has been reported in the English literature (Hamza et al 2016 ; Okano et al 2015 ; Shaikh et al 2015 ; Sun et al 2016 ; Takahashi et al 2010 ; Wang et al 2017 ; Zhu et al 2014 ). In addition, clinical follow-up information was not available in most cases.…”
Section: Discussionmentioning
confidence: 99%
“…GISTs are typically solid, sometimes with small cystic area developed, but rarely manifest as predominant cystic neoplasms. To date, reports of this uncommon form of GISTs have comprised mostly case reports focusing mainly on its clinical and radiographic features (Hamza et al 2016 ; Okano et al 2015 ; Shaikh et al 2015 ; Sun et al 2016 ; Takahashi et al 2010 ; Wang et al 2017 ; Zhu et al 2014 ). There is very limited information in the literature relating to the pathologic features and prognoses of GISTs undergoing extensive cystic change.…”
Section: Introductionmentioning
confidence: 99%
“…GISTs are typically large tumors, with diameters greater than 10 cm. Okano et al reviewed six reported cases of GIST with cystic changes, and the size of these tumors varied from 6 to 32 cm [ 2 ]. We further reviewed the English and Chinese literature and summarize the reported cases in Table 1 [ 4 , 6 – 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although GISTs only occur in less than 5% of all gastrointestinal tract tumors, they account for 60% of all gastric stromal tumors [ 1 ]. GISTs are typically solid tumors and rarely present with predominantly cystic changes [ 2 ]. Here, we describe a case of giant GIST of the stomach with predominantly cystic changes that was cured with complete surgical resection without regional lymphadenectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Although GIST typically appears as a solid mass, few studies have described myxoid GIST that also shows a plexiform growth pattern[10], and some cases of GIST have shown cystic changes as a result of degeneration or necrosis[11-13]. Thus, it may be difficult to distinguish PF from these GIST by performing EUS only once.…”
Section: Discussionmentioning
confidence: 99%